Pendampingan Pengolahan Lele Menjadi Abon Lele Tanpa Minyak di Desa Sampora, Tangerang - Mulyadi, Melisa; Indriati, Kumala (Jurnal Pengabdian Masyarakat Charitas, 2021)
The community of Sampora village, located in Tangerang, has been able to cultivate catfish. In general, the catfish that is produced is directly sold without being processed. In order to increase the economic value of catfish, it is better if catfish is processed into ready-to-eat food products whose selling price can be higher than the price of raw catfish. One of the catfish processed products that can be made is catfish shredded. Shredded catfish has high protein and low cholesterol levels. In addition, shredded catfish is a durable food, can be processed in various flavors so that it is of great interest to the public. Therefore, through community service activities, the Faculty of Engineering collaborates with Village-Owned Enterprises (BUMDES), Sampora Village to provide counseling / assistance for mothers to process catfish into catfish floss without using oil. During this pandemic, assistance was provided in the form of online tutorials. With this assistance, it is hoped that the women of Sampora village can produce shredded catfish products that can be sold in food stalls prepared by BumDes.